Potencial da semente de nêspera (Eriobotrya japonica) na estabilidade oxidativa de produtos de jundiá (Rhamdia quelen) - Piccolo, Jaqueline (2014)
This study aimed to evaluate the effect of the loquat seed extract on oxidative stability of catfish fillets, pate and meatballs, during storage. We evaluated the antioxidant and antimicrobial in vitro activity of loquat seed extracts obtained by different extraction using different solvents and ultrasound treatment. This was followed by evaluating the applicability of loquat seed extracts on oxidative stability of frozen catfish fillets (extracts obtained with 70% acetone and rotaevaporated; AE); on catfish based-pates refrigerated stored (hydroethanolic extract; EE) and on catfish based-meatballs, pre-cooked and frozen stored. Acetone extracts showed the highest total phenolics and total tannins content. Ultrasound treatment improved total phenolic content in 70% acetone extraction and FRAP activity in 35% and 70% acetone extracts. No antimicrobial activity was observed in extracts. The 70% acetone extract was indicated as the one with more significant antioxidant properties. In fish fillets treated with AE, ascorbic acid containing formulation had higher conjugated dienes (CD) than the control and AE-treated pates at 6 months of storage, and presented higher thiobarbituric acid reactive substances (TBARS) than the 400 ppm treated fish fillet at 9 months of storage. However, CD and TBARS had similar values among treatments at 12 months. The protein carbonyl (PC) content increased until 12 months compared to 0 months, however, had no treatment effect. There was a decrease of a* values in all periods and an increase of b* values at 9 and 12 months. The evaluated concentrations of AE were not able to slow lipid and protein oxidation in fish fillets frozen stored, however, did not alter chemical composition or acceptability of fish fillets at 0 months of storage. In catfish based-pates treated with EE, the CD and peroxide values (PV) increased during storage, however, were similar in all treatments after 35 days. TBARS content was not affected by EE. There was a linear increase in PC content in pates over storage. At evaluated concentrations, EE was not able to inhibit or reduce the lipid and protein oxidation in fish pates refrigerated stored. In catfish based-meatballs prepared with AE-treated fish fillets, PV and TBARS decreased over storage time due to high values at initial times assigned to cooking and mincing. Ascorbic acid and 800 ppm containing formulations had higher PV than control formulation, decrease of a* values and increase of b* values over frozen storage. PC content increased over storage time, paralleled to the hardness, with no treatment effect. In the tested concentrations, AE was not able to inhibit the lipid and protein oxidation or to prevent the color change of pre-cooked fish meatballs, and ascorbic acid and 800 ppm formulations showed pro-oxidant effects.